1983
DOI: 10.1288/00005537-198309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Histological acoustic tumor involvement of the viith nerve and multicentric origin in the viiith nerve

Abstract: The surgical plane between the VIIth nerve and acoustic tumor is often elusive. This histological relationship was reviewed in three patients who underwent VII-VII neuroanastomosis at tumor removal disclosing an inseparable surgical plane in two. In the third patient, tissue sections did not accurately show the relationship. In all three, surgical planes were not apparent at tumor removal. Another patient had a second, isolated tumor in the same VIIIth nerve proximally at the brain stem root entry zone. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…Our figures for residual tumor follow the criterion that the MRI image with a round profile and nodular mass 13.2% (7/53) in the group with a follow-up of 3 years or less and 2.1% (1/46) in the group with a follow-up more than 3 years. Most of the tumor-positive findings were in the group with a 5-to 7-year postoperative interval.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Our figures for residual tumor follow the criterion that the MRI image with a round profile and nodular mass 13.2% (7/53) in the group with a follow-up of 3 years or less and 2.1% (1/46) in the group with a follow-up more than 3 years. Most of the tumor-positive findings were in the group with a 5-to 7-year postoperative interval.…”
Section: Resultssupporting
confidence: 72%
“…Four patients presented a linear enhancement on the walls of the meatotomy (nos. 11,12,13) or along the course of the acoustico-facial bundle (no. 4), which did not change at the follow-up MRI 1 year later.…”
Section: Resultsmentioning
confidence: 99%
“…However, the cisternal arachnoid membranes anatomy and its relationship with cranial nerves are controversial, especially because of the difficulty preserving the membranes on cadaveric specimens. The epiarachnoid or subarachnoid origin of VS has been subject of discussion and the presence of an arachnoid surgical plane between tumor and cranial nerves questioned by some authors 17,18,19,20,21,22,23,24,25 . This is not what we have experienced during the surgical procedures, where the arachnoid membrane is used as a protection to preserve the facial nerve anatomically and functionally.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies exist that examine the interface between facial nerve and tumor, and all demonstrate lack of such interface in at least parts of the tumor, if not in all observable parts of the tumor histologically. 51,56 Jääskeläinen et al 51 found that where the facial nerve trunk is attached to the surface of the tumor, nerve fibers in the contact area are either abutted directly against tumor cells or penetrated into the tumor tissue. Because these studies examined the histology of large VSs almost exclusively, they are particularly relevant to the current management paradigm for VS because the larger the tumor, the more likely it becomes a surgical candidate.…”
Section: Tumor-nerve Interface During Vs Surgerymentioning
confidence: 99%